Short Communication: Application of artificial reefs for fisheries enhancement in Probolinggo, Indonesia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Isroni W, Samara SH, Santanumurti MB. 2019. Short Communication: Application of artificial reefs for fisheries enhancement in Probolinggo, Indonesia. Biodiversitas 20: 2273-2278. Overfishing is one of the biggest challenges in the fisheries sector in Probolinggo, Indonesia. The fish apartment (artificial reefs) was one of the solutions to increase the fish resource since it serves as the habitat for fish to live, spawn, and search for food. In this study, the fish apartment was installed in Probolinggo (Karang Katon and Dringu Beach) from 2017 to 2018. This study showed that five fish species (Caesio cuning, Acanthurus achilles, Acanthurus albipectoralis, Sphyraena jello, and Apagon novemfasciatus) were found in Karang Katon while four species (Chaetodon octofasciatus, Chromobotia macracanthus, Nemipterus japonicas, and Lates calcarifer) lived in Dringu Beach. From a total of 333 fishes, A. achilles was the species with the highest composition level of 51.65% (172) in Karang Katon station. In Dringu Beach station, C. octofasciatus had the highest fish species composition level of 46% (183) from a total of 402 fishes. The diversity index and dominance index in Karang Katon station were low at-1.280 and 0.343, respectively. The diversity index and dominance index in Dringu Beach station were also low at -1.115 and 0.3503. A. achilles had the highest density of 34.4 ind/m3 in Karang Katon station while C. octofasciatus had the highest species density of 36.6 ind/m3 in Dringu Beach Station. From this study, it could be concluded that artificial reefs application enhanced the fisheries in Probolinggo, Indonesia, and help its sustainability.
Keywords: Density, diversity index, dominance index, fish apartment, Probolinggo